2002
DOI: 10.1352/0047-6765(2002)040<0390:isiaap>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Supports in Assessment and Planning

Abstract: A systematic approach for addressing the support needs of persons with mental retardation and related developmental disabilities is presented and a new scale to measure individual differences in support needs described. The process employed in developing the scale is explained, including the establishment of a typology of support areas that was drawn from a review of the professional literature, a validation process using Q-sort methodology, and a pilot field test. Critical issues and practical challenges asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
0
15

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 3 publications
9
86
0
15
Order By: Relevance
“…Second, intercorrelations were computed between the eight QOL-domains and the total score for each version of the Scale. If the subscales do measure the same construct, coefficients are expected to be moderate or high, or about .4 to .9 (MacEachron 1982 cited in Thompson et al 2002). Table 3 presents the inter-correlation coefficients for the Self Report version, and Table 4 for the Direct Observation version.…”
Section: Principle # 3: Items Should Be Constructed In a Methodsologicmentioning
confidence: 99%
“…Second, intercorrelations were computed between the eight QOL-domains and the total score for each version of the Scale. If the subscales do measure the same construct, coefficients are expected to be moderate or high, or about .4 to .9 (MacEachron 1982 cited in Thompson et al 2002). Table 3 presents the inter-correlation coefficients for the Self Report version, and Table 4 for the Direct Observation version.…”
Section: Principle # 3: Items Should Be Constructed In a Methodsologicmentioning
confidence: 99%
“…The 'normalization' principle [5,6] challenged this, asserting PWID are entitled to an 'ordinary life', including intimate relationships [7]. This became enshrined in the United Nations Convention on the Rights of Persons with Disabilities [8] and the UK government's 'Valuing People' white paper [9], both stating that PWID have the same rights to marriage and relationships as anyone else.…”
Section: Introductionmentioning
confidence: 99%
“…The SIS is a multidimensional instrument that can be used to assess support needs, determine the intensity of the support that is needed, monitor progress, and evaluate outcomes. The SIS assesses support requirements according to eight support areas: home living, community living, life-long learning, employment, health and safety, social behaviour, protection, and advocacy (57 items); four medical areas: respiratory care, feeding assistance, skin care, and 'other exceptional medical needs'(15 items); four challenging behaviour areas: externally directed destructiveness, self-directed destructiveness, sexual problem behaviour, and 'other challenging behaviours' (13 items 37 Care itself is not the issue, but experienced burden of care SIS 44 Care itself is not the issue, but support needed to provide care AAQ 50 Care itself is not the issue, but time and assistance needed to provide care PEDI, Pediatric Evaluation of Disability Inventory; WeeFIM, Funtional Independence Measure for Children; HUI, Health Utility Index; LIFE-H, Life Habits Assessment; LAQ, Lifestyle Assessment Questionnaire; SIS, Supports Intensity Scale; AAQ, Amount of Assistance Questionnaire. However, several studies have reported an urgent need to express the consequences of these conditions also in terms of need for additional care, as this provides insight into the efforts the parents and the community might face in the future and contributes to medical decision-making, resource policies, and quality assurance.…”
Section: Life-hmentioning
confidence: 99%